Ministernotomy repair of inadvertent proximal right subclavian artery injury following right internal jugular central venous catheter insertion. Issue 4 (22nd April 2022) - Thet, Myat Soe; Kyaw Tun, Jimmy; Oo, Aung Ye; Lopez-Marco, Ana
Abstract : A man in his 60s was referred for urgent coronary artery bypass grafting (CABG) procedure following acute coronary syndrome. After induction of general anaesthesia, right jugular venous catheterisation under two-dimensional ultrasound guidance was planned as part of perioperative management. While obtaining vascular access, the pulsatile flow was noted once the dilator was inserted, having to abandon the procedure and immediately apply manual pressure. CT angiogram showed proximal right subclavian artery injury with active contrast extravasation and resultant large haematoma in the neck. The patient underwent urgent exploration of the injured vessel through a J-shaped ministernotomy, and primary repair of the artery was performed. The patient recovered from the procedure without any complications. He continued to stay in the hospital for a few days, afterwards, he underwent the initially planned CABG surgery. He was discharged home on day 5 after surgery without further concerns.